CHEMICAL FEATURES OF DARK MIСAS FROM CALCITE-NEPHELINE-FELDSPAR PEGMATITES OF THE ILMENOGORSKY ALKALINE BLOCK (SOUTH URALS) - S. V. Cherednichenko (Минералогия)
The composition and structure of micas of the annite–phlogopite and siderophyllite– eastonite series in calcite-nepheline-feldspar pegmatites of the Ilmenogorsky miaskite block are studied. The composition of mica of the annite–phlogopite series depends on the formation conditions of pegmatites. The nepheline-feldspar pegmatite with a rock-forming calcite (mine no. 125) contains annite with higher Fe content (Ftot 0.67–0.73). A pegmatite with late calcite (mine no. 16) contains less ferruginous annite (Ftot 0.52–0.63) and phlogopite (Ftot 0.32–0.50). The mica of the annite-phlogopite series exhibits a direct correlation between the Fetotal and Al contents. The mica of the siderophyllite–eastonite series in calcitenepheline-feldspar pegmatites formed later in assemblage with minerals of the pyrochlore group, baddeleyite, calcite, fluorite, magnetite and Nb-bearing rutile. The Fe content of micas affects the shift of the Raman bands in the studied Samples. Ferruginous siderophyllite, eastonite and their barium varieties are identified for the first time for the Ilmenogosrky-Vishnevogorsky complex.